2019
DOI: 10.1021/acs.iecr.9b03198
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Phase Behavior of Alcohols, Aromatic Alcohols, and Their Mixtures Using the Modified Group-Contribution Perturbed-Chain Statistical Associating Fluid Theory

Abstract: The modified group-contribution perturbed-chain statistical associating fluid theory (PC-SAFT) has been extended to model the phase equilibria of alcohols, branched alcohols, aromatic alcohols, and their mixtures. The parameterization has been implemented based on some physical arguments. The association energy of linear alcohols was fixed to the average experimental value, while this parameter for aromatic alcohols was directly estimated from the trimer hydrogen binding energy as evidenced by several experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…This is because other authors may have made different choices regarding the following: temperature ranges from which data were taken, quantities of data points per species used, spacing between data points and data sources chosen. The average %AAD values of saturated vapor pressure and saturated liquid densities (or volumes) were 2.13 and 1.76% for polar GC-SAFT-0, 2.76 and 1.46% for mg-SAFT, 5.20 and 1.80% for hetero-GC-SAFT-VR, and 2.19 and 1.09% for SAFT-γ SW, respectively. Notably, SAFT-γ SW does not use DIPPR as a data source.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…This is because other authors may have made different choices regarding the following: temperature ranges from which data were taken, quantities of data points per species used, spacing between data points and data sources chosen. The average %AAD values of saturated vapor pressure and saturated liquid densities (or volumes) were 2.13 and 1.76% for polar GC-SAFT-0, 2.76 and 1.46% for mg-SAFT, 5.20 and 1.80% for hetero-GC-SAFT-VR, and 2.19 and 1.09% for SAFT-γ SW, respectively. Notably, SAFT-γ SW does not use DIPPR as a data source.…”
Section: Resultsmentioning
confidence: 96%
“…These are then treated as individual molecules in the respective model frameworks. For example, this was done in developing the GC-SAFT group interaction parameters for several hydrocarbon series and alcohols, GC-SAFT-VR group interaction parameters for common nonassociating and associating organic functional groups, , as well as mg-SAFT group interaction parameters for several hydrocarbon series , and alcohols …”
Section: Parameterization Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Phenol and its mixtures present a major challenge for modeling. As discussed elsewhere, in addition to dipolar interactions, this compound exhibits complex association phenomena, which can be considered to be similar to carboxylic acids. Previously, Schmelzer et al demonstrated that accounting for association version of Cubic Schmidt–Wenzel EoS with system-specific and temperature-dependent binary adjustable parameter k 12 can correlate VLE and LLE in several n -alkane + phenol binary systems.…”
Section: Resultsmentioning
confidence: 95%
“…This approach resulted in reasonably accurate correlation of some data and less impressive modeling of others, such the upper critical solution temperatures (UCSTs), which were systematically overestimated. Later on, Nguyen Huynh et al obtained particularly accurate results for LLE in n -alkane–phenol systems using the modified group-contribution PC-SAFT which simultaneously accounts for dipolar and 2B association interactions. Different system-specific k 12 values were used for accurate correlation of VLE in the same systems.…”
Section: Resultsmentioning
confidence: 99%